Semiotic Analysis In Xo, Kitty Netflix Series - Artamevia, Tiara; Maca, Sudirman; Rosmawati, Rosmawati (Fakultas Sastra, Universitas Bosowa, 2024)
The purpose of this study was to identify and interpret the relationship between signifier and signified in verbal and visual aspects on posters, trailers, and scenes of the Netflix series XO, Kitty. The research method used by the researcher was descriptive qualitative analysis with a semiotic approach. The data were collected by watching the Netflix series, capturing the screen and taking notes, collecting verbal and visual aspects, and analysed based on the signifiers and signs by applying Ferdinand de Saussure's semiotic theory. The results show that in posters and visual elements such as backgrounds, character poses, and graphic elements functioned as markers that formed certain meanings regarding the theme and atmosphere of the series. In the trailers, the use of dialogue and visual montage identified the signifiers in which introduced the main characters and the conflicts that they faced. Analysis of scenes in the first episode revealed how verbal (dialogue) and visual (cinematography, setting) elements worked together to build narrative and characterization